Estudo comparativo dos efeitos dos Espaços de Circulação e Permanência de Pedestres (ECPP) sobre o manejo das águas de chuva - Parra, Geovana Geloni (2016)
The cities have grown significantly and in a disorderly way, without minimum urban planning, which has provoked to urban and environmental problems. Among many consequences of this growth, high soil waterproofing features highlight due to the consequences it brings, as the occurrence of floods, floods and spread of waterborne diseases. Much of the runoff of rainwater comes from the paved soil, and is possible observe that about 20% of the urban area of a city is paved with the function of serving as circulation area of pedestrians or vehicles, according to the Federal Law No. 6766 of 19 December 1979 which provides for the division of urban soil and other measures (BRAZIL, 1979). In this context the objective of this research is the study of the effects of the spaces of Circulation and Permanence Pedestrians (ECPP) on the management of rainwater, with the empirical object one experimental watershed located on the campus of UFSCar in São Carlos / SP, and two areas urbanized in the city of Sao Jose do Rio Preto / SP. For this, it was made the identification of different types of floors, characterization and hydrological efficiency, research in academic papers and catalogs of suppliers, and analyze the areas and conditions of ECPPs within the perimeters of study under the hydrologic context, design, implementation, and maintenance costs. The findings evaluate the effects of ECPPs on the management of rainwater, and compare the results between the three ECPPs. These results show that the ECPP located in USFCar contributes 6% to runoff, while the ECPP Pedestrian street 35% and ECPP Neighborhood 9% to project parties were adopted that destined runoff for grassed areas or permeable floors these scenarios would be 2% contribution to ECPP UFSCar, 0.2% of flow for ECPP Pedestrian Street and 2% for ECPP Neighborhood. So is possible reduce runoff using hydrologically functional floors, implementing and using the green areas as a design element, providing knowledge of data and materials that can contribute to new ways to plan and execute the ECPPs.